Penguins - Arlon, Penelope (New York : Scholastic, 2012)
This book is about penguins. Meet every kind of penguin up close. Watch them walk, talk, make friends, share meals, and raise fluffy chicks. Journey to Antarctica and found out how penguins there survive natural and man-made dangers in their icy home.